2019
DOI: 10.1093/neuonc/noz031
|View full text |Cite
|
Sign up to set email alerts
|

Cystathionine as a marker for 1p/19q codeleted gliomas by in vivo magnetic resonance spectroscopy

Abstract: Background. Codeletion of chromosome arms 1p and 19q (1p/19q codeletion) highly benefits diagnosis and prognosis in gliomas. In this study, we investigated the effect of 1p/19q codeletion on cancer cell metabolism and evaluated possible metabolic targets for tailored therapies. Methods. We combined in vivo 1 H (proton) magnetic resonance spectroscopy (MRS) measurements in human gliomas with the analysis of a series of standard amino acids by liquid chromatography-mass spectroscopy (LC-MS) in human glioma biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 41 publications
8
53
0
1
Order By: Relevance
“…The cystathionine concentration in gliomas ranged from 0.2 mM to 4.1 mM, as reported previously . Cystathionine was not detectable in normal brain tissue (Figure ).…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…The cystathionine concentration in gliomas ranged from 0.2 mM to 4.1 mM, as reported previously . Cystathionine was not detectable in normal brain tissue (Figure ).…”
Section: Resultssupporting
confidence: 81%
“…The cystathionine signal at 2.72 ppm, as well as the 2HG signal at 4 ppm, are detected with no overlap with other metabolites when using edited MRS. The cystathionine signal was unexpectedly observed during our previous study focusing on the measurement of 2HG and identified as cystathionine based on the agreement with phantom and simulated spectra . Whereas the editing efficiency is optimal for 2HG detection using an editing pulse placed at 1.9 ppm, a significant improvement can be achieved with regard to cystathionine detection by tuning the editing pulse frequency.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations